Art History Is Dead; Long Live Art History!. Issue 2 (2nd September 2017) - Kearney, Alison
Abstract: The # RhodesMustFall campaign that began at the University of Cape Town in early 2015, called for the decolonisation of South African university curricula, among other transformations. As a result, many South African academics are questioning the epistemologies that underpin their disciplines. What does the decolonisation of university curricula imply for disciplines in the humanities, art history among them, which were born at the time of colonial expansion and the categorising of knowledge that came with the enlightenment? In this paper I explore some implications of the decolonisation of art history for the ways in which we practise and write art history today. I begin by briefly exploring the origins of the discipline, in order to create a platform from which to consider contemporary art history writing. I then consider the ways in which the decolonisation of the discipline could be understood as the end of art history. A reflection of some of the affordances and limitations of the postcolonial rhetoric in which calls for decolonisation are framed, leads me to consider methods of writing art history that could be construed as acts of decolonisation. I conclude by suggesting that one way to decolonise the discipline is to foreground the author's subjective voice when writing arts histories.